The anatomy of seismic signalling: morphological adaptations of the hind limb in drumming and non-drumming African mole-rats (Bathyergidae) - Sahd, Lauren (Stellenbosch : Stellenbosch University, 2021., 2021)
Thesis (PhD)--Stellenbosch University, 2021.